A production process for co-producing titanium nitride and ferrosilicon nitride
By using the heat generated by the silicon nitriding reaction in the ferrosilicon nitriding self-propagation furnace to promote the carbon-thermal reduction and nitriding of the semi-finished titanium nitride products, the problems of high energy consumption and heat loss of titanium nitride production in the prior art are solved, and efficient and low-cost titanium nitride production are achieved.
Patent Information
- Application Number
- CN202411212324.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-30
AI Technical Summary
In the prior art, the production of titanium nitride is high in energy consumption, and excessive heat is generated during the nitriding of ferrosilicon, resulting in melting silicon and heat loss.
By adopting the co-production process, the synthetic titanium nitride semi-finished products and ferrosilicon powders are placed layer by layer in the ferrosilicon nitride self-propagation furnace, and the heat generated by the silicon nitride reaction in the ferrosilicon powder is used to promote the synthetic titanium nitride semi-finished products to undergo carbon thermal reduction and nitriding to generate titanium nitride.
It reduces the energy consumption of titanium nitride production, reduces heat loss, improves the production efficiency of titanium nitride, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of co-production of titanium nitride and ferrosilicon nitride, and specifically to a production process for co-producing titanium nitride and ferrosilicon nitride. Background Art
[0002] Titanium nitride is a high melting point compound with a melting point of 2950℃. It has good wear resistance and a Mohs hardness of 8-9. It has good stability and does not react with metals such as iron, chromium, calcium, and magnesium at high temperatures. It also does not react with acidic slag and alkaline slag in carbon monoxide and nitrogen atmospheres. Therefore, adding titanium nitride or titanium-containing materials that can generate titanium nitride at the operating temperature to the tapping mud for iron smelting can improve the corrosion resistance of the tapping mud and extend the iron-tapping time. At present, titanium dioxide, high titanium slag, or titanium slag produced by smelting ferrotitanium with titanium elements is generally used. The purpose of adding titanium dioxide, high titanium slag, or titanium slag produced by smelting ferrotitanium is that at high temperatures, titanium oxide will react with carbon in the tapping mud to generate titanium nitride or titanium carbonitride, which plays a role in enhancing the corrosion resistance of the tapping mud. But it also brings negative effects. The titanium element in titanium dioxide, high titanium slag or titanium slag produced by smelting titanium iron exists in the form of oxides. At high temperature, it reacts with the carbon in the cannon mud to form titanium nitride or titanium carbonitride, which destroys the carbon structure of the cannon mud and reduces the bonding strength of the cannon mud. The reaction formula is as follows: 2TiO2+4C+N2=2TiN+4CO. Using titanium nitride raw materials directly added to the cannon mud can improve the corrosion resistance of the cannon mud without affecting the high temperature strength of the cannon mud.
[0003] Currently, titanium nitride is produced by high-temperature nitridation of titanium powder on the market, but the cost is too high. Using low-cost titanium dioxide-containing raw materials to synthesize titanium nitride at high temperature requires a lot of electricity. This method requires about 5,000 degrees of electricity to synthesize one ton of titanium nitride raw materials. Excessive heat generated during the ferrosilicon nitridation process will cause molten silicon, and heat dissipation measures are often required. The heat cannot be effectively utilized, resulting in heat loss. Therefore, it is very important to develop a low-cost titanium nitride raw material production process. Summary of the invention
[0004] In view of this, the present application provides a production process for the co-production of titanium nitride and ferrosilicon nitride, which solves the problem of high energy consumption in the production of titanium nitride in the prior art. However, in the nitridation process of producing ferrosilicon nitride, excessive heat is generated by the nitridation of silicon in ferrosilicon, which can easily cause the phenomenon of molten silicon, and measures need to be taken to dissipate heat, thus causing the technical problem of heat loss.
[0005] The present application provides a production process for the co-production of titanium nitride and ferrosilicon nitride, which comprises the following steps: firstly, preparing a raw material for synthesizing titanium nitride in a certain proportion, and then pressing and molding the prepared raw material for synthesizing titanium nitride and drying it to form a semi-finished product for synthesizing titanium nitride; then, loading the pressed and molded semi-finished product for synthesizing titanium nitride into a self-propagating ferrosilicon furnace for nitriding, and spreading a layer of ferrosilicon powder on the pressed and molded semi-finished product for synthesizing titanium nitride, one layer of the pressed and molded semi-finished product for synthesizing titanium nitride, and then placing the layer by layer; then, sealing the self-propagating ferrosilicon furnace for nitriding, introducing nitrogen, igniting the self-propagating furnace, and naturally cooling the self-propagating ferrosilicon furnace to below 200° C. after the reaction is complete, and then taking the self-propagating ferrosilicon furnace out of the furnace; wherein, the pressed and molded semi-finished product for synthesizing titanium nitride and the ferrosilicon powder are loaded into the self-propagating furnace in a certain proportion, and the heat generated by the silicon-nitrogen combination reaction in the ferrosilicon powder is utilized to promote the carbon thermal reduction nitridation of the semi-finished product for synthesizing titanium nitride to generate titanium nitride.
[0006] In one embodiment, the weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is (1-3):(9-7).
[0007] In one embodiment, the weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 1:9.
[0008] In one embodiment, the weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 2:8.
[0009] In one embodiment, the weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 3:7.
[0010] In one embodiment, the preparation steps of the block titanium nitride include: the preparation steps of the pressed synthetic titanium nitride semi-finished product include: step (1), taking 100 parts of titanium dioxide-containing raw material, 25-30 parts of carbonaceous reducing agent, and 3-6 parts of binder into a mixer and mixing them thoroughly for 5-15 minutes, then adding a certain amount of solvent and mixing for 5-15 minutes, discharging the material, using a ball press to press the synthetic titanium nitride raw material into a spherical shape, and / or using a brick press to press the synthetic titanium nitride raw material into a brick shape; step (2), putting the brick-shaped and / or spherical synthetic titanium nitride raw material pressed in step (1) into a drying kiln or drying box, and drying it at a temperature of 110-200°C for 22-26 hours to obtain a dry pressed synthetic titanium nitride semi-finished product.
[0011] In one embodiment, in step (1), the titanium dioxide-containing raw material includes one or more of titanium dioxide, high-titanium slag, acid titanium slag, and titanium concentrate; preferably, the titanium dioxide content in the titanium dioxide is greater than 98%; the titanium dioxide content in the high-titanium slag is greater than 90%; the titanium dioxide content in the titanium concentrate is greater than 48%; and the titanium dioxide content in the acid titanium slag is greater than 74%.
[0012] In one embodiment, in step (1), the carbonaceous reducing agent includes one or more of carbon black, petroleum coke powder, and graphite powder.
[0013] In one embodiment, in step (1), the binder includes one or more of phenolic resin, dextrin, pregelatinized starch, and white sugar.
[0014] In one embodiment, in step (2), the solvent is alcohol or water.
[0015] The present application provides a production process for the co-production of titanium nitride and ferrosilicon nitride. First, raw materials for synthetic titanium nitride are prepared in a certain proportion, and then the prepared raw materials for synthetic titanium nitride are pressed into shape and dried to form a semi-finished product for synthetic titanium nitride; then the pressed and shaped semi-finished product for synthetic titanium nitride is loaded into a ferrosilicon nitriding self-propagating furnace, and a layer of ferrosilicon powder is spread on the pressed and shaped semi-finished product for synthetic titanium nitride, one layer of the pressed and shaped semi-finished product for synthetic titanium nitride, and one layer of ferrosilicon powder is placed layer by layer, and then the ferrosilicon nitriding self-propagating furnace is sealed and nitrogen is introduced to ignite the reaction in the self-propagating furnace, and after the reaction is complete, the self-propagating furnace is naturally cooled to below 200° C. and taken out of the furnace; wherein the pressed and shaped semi-finished product for synthetic titanium nitride and ferrosilicon powder are loaded into the self-propagating furnace in a certain proportion, and the heat generated by the silicon-nitride combination reaction in the ferrosilicon powder is used to promote the carbon thermal reduction nitridation of the semi-finished product for synthetic titanium nitride to generate titanium nitride. Since too much heat is generated by silicon nitridation during the ferrosilicon nitriding process, it is easy to cause molten silicon, and measures need to be taken to dissipate heat. The heat cannot be effectively utilized, resulting in heat loss. Titanium nitride is synthesized by high-temperature electrothermal synthesis using titanium-containing oxides. The titanium nitride raw materials consume a lot of electricity, which leads to high production costs. The present application combines the production processes of ferrosilicon nitride and titanium nitride, and utilizes the heat generated by the silicon-nitride reaction of the ferrosilicon powder to promote the carbon thermal reduction nitridation of the synthetic titanium nitride semi-finished product to generate titanium nitride, thereby greatly reducing the production cost. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0017] Example 1
[0018] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0019] Step (1), weighing 100 parts of titanium dioxide, 30 parts of carbon black, and 5 parts of dextrin, putting the titanium dioxide, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% of water, and mixing them for another 15 minutes, and then putting the raw materials for synthesizing titanium nitride into a brick press and pressing them into a brick shape;
[0020] Step (2), placing the brick-shaped synthetic titanium nitride raw material pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride raw material to below 0.5% to obtain a dry pressed synthetic titanium nitride semi-finished product.
[0021] 2. Load the semi-finished product of synthetic titanium nitride pressed after drying into the self-propagating furnace of ferrosilicon nitriding, spread a layer of ferrosilicon powder on the semi-finished product of synthetic titanium nitride pressed, and then place another layer of semi-finished product of synthetic titanium nitride pressed on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the semi-finished product of synthetic titanium nitride pressed, to form a layer of semi-finished product of synthetic titanium nitride pressed and a layer of ferrosilicon powder, until it is laid to the top of the self-propagating furnace of ferrosilicon nitriding, and the weight of the semi-finished product of synthetic titanium nitride pressed and the ferrosilicon powder loaded into the self-propagating furnace of ferrosilicon nitriding is 2. The ratio is 3:7, and then the silicon iron nitride self-propagating furnace is sealed, and nitrogen is introduced, and the silicon iron nitride self-propagating furnace is ignited for reaction. After the reaction is complete, the self-propagating furnace is naturally cooled to below 200°C, the kiln door is opened, and the furnace is taken out to obtain titanium nitride and silicon iron nitride. The nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 1 is greater than 97%.
[0022] 3. A ferrosilicon nitriding self-propagating furnace that produces ferrosilicon nitride using ferrosilicon powder. One ferrosilicon nitriding self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitride combination reaction of ferrosilicon powder can be used to synthesize 150 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced.
[0023] Example 2
[0024] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0025] Step (1), weighing 100 parts of 320-mesh high-titanium slag fine powder, 28 parts of 320-mesh burned petroleum coke fine powder, and 5 parts of dextrin, putting the high-titanium slag fine powder, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% of water, and mixing them for another 15 minutes, and then putting the raw materials for synthesizing titanium nitride into a brick press and pressing them into a brick shape;
[0026] Step (2), placing the brick-shaped synthetic titanium nitride raw material pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride raw material to below 0.5%, thereby obtaining a dry pressed synthetic titanium nitride semi-finished product.
[0027] 2. Load the semi-finished synthetic titanium nitride product pressed and dried into a ferrosilicon nitriding self-propagating furnace, spread a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product, and then place another layer of pressed synthetic titanium nitride semi-finished product on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product to form a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product until it is laid to the top of the ferrosilicon nitriding self-propagating furnace. The weight ratio of the pressed synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 3:7. Then the ferrosilicon nitriding self-propagating furnace is sealed, nitrogen is introduced, and the ferrosilicon nitriding self-propagating furnace is ignited for reaction. The self-propagating furnace is reacted. After the reaction is complete, the self-propagating furnace is naturally cooled to below 200° C. The kiln door is opened and the furnace is taken out to obtain titanium nitride and ferrosilicon nitride. The contents of nitrogen, oxygen, carbon and other elements in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 2 is greater than 90%.
[0028] 3. A ferrosilicon nitriding self-propagating furnace that produces ferrosilicon nitride using ferrosilicon powder. One ferrosilicon nitriding self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitrogen combination reaction of ferrosilicon powder can be used to synthesize 150 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced.
[0029] Example 3
[0030] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0031] Step (1), weighing 100 parts of 320-mesh titanium concentrate fine powder, 29 parts of 320-mesh burned petroleum coke fine powder, and 5 parts of dextrin, putting the titanium concentrate fine powder, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% water and mixing them for 15 minutes, and then putting the raw materials for synthesizing titanium nitride into a brick press and pressing them into a brick shape;
[0032] Step (2), placing the raw material of synthetic titanium nitride pressed into a brick shape in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the raw material of synthetic titanium nitride in the brick shape to below 0.5%, thereby obtaining a dry pressed synthetic titanium nitride semi-finished product.
[0033] 2. Load the semi-finished synthetic titanium nitride product pressed and dried into a ferrosilicon nitriding self-propagating furnace, spread a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product, and then place another layer of pressed synthetic titanium nitride semi-finished product on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product to form a layer of pressed synthetic titanium nitride semi-finished product and a layer of ferrosilicon powder until it is laid to the top of the ferrosilicon nitriding self-propagating furnace. The weight ratio of the pressed synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 3:7. Then the ferrosilicon nitriding self-propagating furnace is sealed, nitrogen is introduced, and the ferrosilicon nitriding self-propagating furnace is ignited for reaction. After the reaction is complete, the self-propagating furnace is naturally cooled to below 200°C, the kiln door is opened, the furnace is taken out, and titanium nitride and ferrosilicon nitride are obtained. Samples are taken and the contents of nitrogen, oxygen, carbon and other elements in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 3 is greater than 70%.
[0034] 3. A ferrosilicon nitride self-propagating furnace that uses ferrosilicon powder to produce ferrosilicon nitride. One ferrosilicon nitride self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitrogen combination reaction of ferrosilicon powder can be used to synthesize 150 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced.
[0035] Example 4
[0036] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0037] Step (1), weighing 100 parts of 320-mesh acid titanium slag fine powder, 23 parts of 320-mesh burned petroleum coke fine powder, and 5 parts of dextrin, putting the titanium dioxide fine powder, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% water and mixing them for 15 minutes, and then putting the raw materials for synthesizing titanium nitride into a brick press and pressing them into a brick shape;
[0038] Step (2), placing the brick-shaped synthetic titanium nitride raw material pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride raw material to below 0.5%, thereby obtaining a dry pressed synthetic titanium nitride semi-finished product.
[0039] 2. Load the semi-finished synthetic titanium nitride product pressed and dried into a ferrosilicon nitriding self-propagating furnace, spread a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product, and then place another layer of pressed synthetic titanium nitride semi-finished product on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product to form a layer of pressed synthetic titanium nitride semi-finished product and a layer of ferrosilicon powder until it is laid to the top of the ferrosilicon nitriding self-propagating furnace. The weight ratio of the pressed synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 3:7. Then the ferrosilicon nitriding self-propagating furnace is sealed, nitrogen is introduced, and the ferrosilicon nitriding self-propagating furnace is ignited for reaction. After the reaction is complete, the self-propagating furnace is naturally cooled to below 200°C, the kiln door is opened, the furnace is taken out, and titanium nitride and ferrosilicon nitride are obtained. Samples are taken and the contents of nitrogen, oxygen, carbon and other elements in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 4 is greater than 80%.
[0040] 3. A self-propagating furnace is used to produce ferrosilicon nitride using ferrosilicon powder. One self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitrogen combination reaction of ferrosilicon powder can be used to synthesize 150 tons of titanium nitride at low cost, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced.
[0041] Example 5
[0042] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0043] Step (1), weighing 100 parts of titanium dioxide, 30 parts of carbon black, and 5 parts of dextrin, putting the titanium dioxide, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% of water, and mixing them for another 15 minutes, and then putting the synthesized titanium nitride raw material into a brick press and pressing it into a brick shape;
[0044] Step (2), placing the brick-shaped synthetic titanium nitride raw material pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride raw material to below 0.5% to obtain a dry pressed synthetic titanium nitride semi-finished product.
[0045] 2. Load the dried pressed synthetic titanium nitride semi-finished product into a ferrosilicon nitriding self-propagating furnace, spread a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product, and then place another layer of pressed synthetic titanium nitride semi-finished product on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product to form a layer of pressed synthetic titanium nitride semi-finished product and a layer of ferrosilicon powder until they are laid to the top of the ferrosilicon nitriding self-propagating furnace, and the pressed synthetic titanium nitride semi-finished product and ferrosilicon powder are loaded into the weight of the ferrosilicon nitriding self-propagating furnace. The amount ratio is 2:8, and then the silicon iron nitride self-propagating furnace is sealed, and nitrogen is introduced, and the silicon iron nitride self-propagating furnace is ignited for reaction. The reaction is complete, and the self-propagating furnace is naturally cooled to below 200°C, and the kiln door is opened. The furnace is taken out to obtain titanium nitride and silicon iron nitride. The nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 5 is greater than 97%.
[0046] 3. A ferrosilicon nitriding self-propagating furnace that produces ferrosilicon nitride using ferrosilicon powder. One ferrosilicon nitriding self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitride combination reaction of ferrosilicon powder can be used to synthesize 100 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced. When the weight ratio of the pressed synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 2:8, the amount of titanium nitride raw material loaded is reduced, and the amount of synthesized titanium nitride is also reduced accordingly.
[0047] Example 6
[0048] 1. Preparation of synthetic titanium nitride semi-finished products:
[0049] Step (1), weighing 100 parts of titanium dioxide, 30 parts of carbon black, and 5 parts of dextrin, putting the titanium dioxide, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% of water, mixing them for another 15 minutes, and then putting them into a brick press to press them into a brick-shaped synthetic titanium nitride semi-finished product;
[0050] Step (2), placing the brick-shaped synthetic titanium nitride semi-finished product pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride semi-finished product to below 0.5%.
[0051] 2. Load the pressed and dried synthetic titanium nitride semi-finished product into a ferrosilicon nitriding self-propagating furnace, spread a layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product, and then place another layer of pressed synthetic titanium nitride semi-finished product on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the pressed synthetic titanium nitride semi-finished product to form a pressed synthetic titanium nitride semi-finished product and a layer of ferrosilicon powder until it is laid to the top of the ferrosilicon nitriding self-propagating furnace. The weight ratio of the brick-shaped synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 1:9. Then the ferrosilicon nitriding self-propagating furnace is sealed, nitrogen is introduced, and the ferrosilicon nitriding self-propagating furnace is ignited for reaction. After the reaction is complete, wait for the self-propagating furnace to naturally cool to below 200°C, open the kiln door, take the product out of the furnace, and obtain titanium nitride and ferrosilicon nitride. Take samples and use nitrogen oxygen meter and other related element analysis instruments to analyze and detect the nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride, and calculate the content of titanium nitride according to the molecular formula of titanium nitride. The content of titanium nitride in the product synthesized by the method of Example 5 is greater than 97%.
[0052] 3. A ferrosilicon nitriding self-propagating furnace that produces ferrosilicon nitride using ferrosilicon powder. One ferrosilicon nitriding self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitride combination reaction of ferrosilicon powder can be used to synthesize 70 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced. When the weight ratio of the pressed synthetic titanium nitride semi-finished product and the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 1:9, the amount of titanium nitride raw material loaded is reduced, and the amount of synthesized titanium nitride is also reduced accordingly.
[0053] Comparative Example 1
[0054] 1. Preparation of semi-finished products of synthetic titanium nitride:
[0055] Step (1), weighing 100 parts of titanium dioxide, 30 parts of carbon black, and 5 parts of dextrin, putting the titanium dioxide, carbon black, and dextrin into a mixer and mixing them for 15 minutes, then adding 20% of water, and mixing them for another 15 minutes, and then putting the raw materials for synthesizing titanium nitride into a brick press and pressing them into a brick shape;
[0056] Step (2), placing the brick-shaped synthetic titanium nitride raw material pressed in step (1) into a drying kiln, and drying it at 110-200° C. for 24 hours to reduce the moisture content of the brick-shaped synthetic titanium nitride raw material to below 0.5% to obtain a dry pressed synthetic titanium nitride semi-finished product.
[0057] 2. Load the semi-finished product of synthetic titanium nitride pressed after drying into the self-propagating furnace of ferrosilicon nitriding, spread a layer of ferrosilicon powder on the semi-finished product of synthetic titanium nitride pressed, and then place another layer of semi-finished product of synthetic titanium nitride pressed on the ferrosilicon powder, and spread another layer of ferrosilicon powder on the semi-finished product of synthetic titanium nitride pressed, to form a layer of semi-finished product of synthetic titanium nitride pressed and a layer of ferrosilicon powder, until it is laid to the top of the self-propagating furnace of ferrosilicon nitriding, and the weight of the semi-finished product of synthetic titanium nitride pressed and the ferrosilicon powder loaded into the self-propagating furnace of ferrosilicon nitriding is 2. The ratio is 4:6, and then the silicon iron nitride self-propagating furnace is sealed, and nitrogen is introduced, and the silicon iron nitride self-propagating furnace is ignited for reaction. After the reaction is complete, the self-propagating furnace is naturally cooled to below 200°C, the kiln door is opened, and the furnace is taken out to obtain titanium nitride and silicon iron nitride. The nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride are analyzed and detected using nitrogen oxygen meters and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in the product synthesized by the method of Example 1 is greater than 75%.
[0058] 3. A ferrosilicon nitriding self-propagating furnace that produces ferrosilicon nitride using ferrosilicon powder. One ferrosilicon nitriding self-propagating furnace can produce 1,000 tons of ferrosilicon nitride annually. It is estimated that the heat generated by the silicon-nitride combination reaction of ferrosilicon powder can be used to synthesize 150 tons of titanium nitride, and at least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced.
[0059] As can be seen from Table 1, the raw materials for synthesizing titanium nitride in Example 1, Example 5 and Example 6 are titanium dioxide and carbon black, and the weight ratio of the semi-finished product of synthesized titanium nitride to ferrosilicon powder added to the ferrosilicon nitriding self-propagating furnace is 3:7; 2:8; 1:9 respectively. After the production process of Examples 1, 5 and 6, the titanium nitride and ferrosilicon nitride prepared are sampled and analyzed and detected by nitrogen oxygen meter and other related element analysis instruments for the nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in Example 1, Example 5 and Example 6 is greater than 97%, which indicates that when a suitable raw material for synthesizing titanium nitride is used and the semi-finished product of synthesized titanium nitride and ferrosilicon powder are added in a ratio of (1-3): (9-7), the content of synthesized titanium nitride is the highest.
[0060] The raw materials for synthesizing titanium nitride in Example 2, Example 3, and Example 4 are respectively high titanium slag + petroleum coke powder; titanium concentrate + petroleum coke powder; acid titanium slag + petroleum coke powder. The titanium nitride and ferrosilicon nitride prepared through the production processes of Examples 2, 3, and 4 are sampled using nitrogen oxygen meters and other related element analysis instruments to measure the contents of nitrogen, oxygen, carbon and other elements in the fired samples of titanium nitride, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in Example 2 is greater than 90%, the content of titanium nitride in Example 3 is greater than 70%; the content of titanium nitride in Example 4 is greater than 80%. Through the production processes of Examples 1-4, products with different titanium nitride content grades can be produced. According to the actual different needs of customers for the content of titanium nitride, any one of the production processes of Examples 1-4 can be selected for production.
[0061] The weight ratio of the semi-finished product of synthetic titanium nitride of comparative example 1 to ferrosilicon powder added to the ferrosilicon nitriding self-propagating furnace is 4:6. The raw materials for synthesizing titanium nitride are titanium dioxide + carbon black. The titanium nitride and ferrosilicon nitride prepared by the production process of comparative example 1 are sampled and analyzed and tested for the nitrogen, oxygen, carbon and other element contents in the fired sample titanium nitride using a nitrogen oxygen meter and other related element analysis instruments, and the content of titanium nitride is calculated according to the molecular formula of titanium nitride. After detection and calculation, the content of titanium nitride in comparative example 1 is greater than 75%. , which is far lower than the content of titanium nitride in Example 1. Therefore, when the semi-finished product of synthetic titanium nitride and ferrosilicon powder are added to the ferrosilicon nitriding self-propagating furnace in a weight ratio of (1-3): (9-7), the heat generated by the silicon-nitride reaction of 7-9 parts of ferrosilicon powder is sufficient to promote the carbon thermal reduction nitridation of 1-3 parts of the semi-finished product of synthetic titanium nitride to generate titanium nitride, while the heat generated by the silicon-nitride reaction of 6 parts of ferrosilicon powder is insufficient to promote the carbon thermal reduction nitridation of 4 parts of the semi-finished product of synthetic titanium nitride to generate titanium nitride.
[0062] Table 1 Comparison of results of Examples 1-6
[0063]
[0064] The raw material of synthetic titanium nitride of the present application is pressed and formed, and then dried to form a semi-finished product of synthetic titanium nitride raw material, and then the pressed and formed semi-finished product of synthetic titanium nitride is loaded into a silicon-iron nitriding self-propagating furnace, and a layer of silicon-iron powder is spread on the pressed and formed semi-finished product of synthetic titanium nitride. A layer of pressed and formed semi-finished product of synthetic titanium nitride and a layer of silicon-iron powder are placed layer by layer, and the heat generated by silicon-iron powder in the silicon-nitride reaction is used to promote the carbon thermal reduction nitridation of synthetic titanium nitride raw material to generate titanium nitride. A silicon-iron nitriding self-propagating furnace can produce 1,000 tons of silicon-iron nitride per year, and it is estimated that the heat generated by silicon-iron powder in the silicon-nitride reaction can be used to synthesize 70-150 tons of titanium nitride. At least 5,000 kWh of electricity can be saved for each ton of titanium nitride produced, which greatly saves electricity consumption and reduces production costs.
[0065] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A production process for co-producing titanium nitride and ferrosilicon nitride, characterized in that: First, a synthetic titanium nitride raw material is prepared according to a certain ratio, and then the prepared synthetic titanium nitride raw material is pressed and dried to form a semi-finished synthetic titanium nitride product; then the pressed synthetic titanium nitride semi-finished product is loaded into a ferrosilicon nitriding self-propagating furnace, a layer of ferrosilicon powder is laid on the pressed synthetic titanium nitride semi-finished product, and a layer of ferrosilicon powder is laid layer by layer on the pressed synthetic titanium nitride semi-finished product, and then the ferrosilicon nitriding self-propagating furnace is sealed and nitrogen is introduced, and the self-propagating furnace is ignited, and the ferrosilicon nitriding self-propagating furnace is naturally cooled to below 200° C. when the reaction is complete and then taken out of the furnace; The pressed semi-finished synthetic titanium nitride product and the ferrosilicon powder are loaded into a self-propagating furnace in a certain ratio, and the heat generated by the silicon-nitride reaction of the ferrosilicon powder is used to promote the carbon thermal reduction nitridation of the semi-finished synthetic titanium nitride product to generate titanium nitride; The titanium nitride raw material is 100 parts of titanium dioxide-containing raw material, 25-30 parts of carbonaceous reducing agent, and 3-6 parts of binder; The weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is (1-3): (9-7).
2. A production process for co-producing titanium nitride and ferrosilicon nitride according to claim 1, characterized in that: The weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 1:
9.
3. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 1, characterized in that: The weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 2:
8.
4. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 1, characterized in that: The weight ratio of the pressed synthetic titanium nitride semi-finished product to the ferrosilicon powder loaded into the ferrosilicon nitriding self-propagating furnace is 3:
7.
5. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 1, characterized in that: The preparation steps of the semi-finished product of the pressed synthetic titanium nitride include: Step (1), taking 100 parts of titanium dioxide-containing raw material, 25-30 parts of carbonaceous reducing agent, and 3-6 parts of binder into a mixer and mixing them for 5-15 minutes, then adding a certain amount of solvent and mixing for 5-15 minutes, discharging the material, using a ball press to press the raw material for synthesizing titanium nitride into a spherical shape, and / or using a brick press to press the raw material for synthesizing titanium nitride into a brick shape; Step (2), placing the raw material of synthetic titanium nitride in the shape of a brick and / or a sphere pressed in step (1) into a drying kiln or drying box, and drying it at a temperature of 110-200° C. for 22-26 hours to obtain a semi-finished product of synthetic titanium nitride pressed into the shape of a brick and / or a sphere.
6. A production process for co-producing titanium nitride and ferrosilicon nitride according to claim 5, characterized in that: In the step (1), the titanium dioxide-containing raw material includes one or more of titanium dioxide, high-titanium slag, acid titanium slag, and titanium concentrate.
7. A process for co-producing titanium nitride and ferrosilicon nitride according to claim 6, characterized in that: The titanium dioxide content in the titanium dioxide is greater than 98%; the titanium dioxide content in the high-titanium slag is greater than 90%; the titanium dioxide content in the titanium concentrate is greater than 48%; and the titanium dioxide content in the acid titanium slag is greater than 74%.
8. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 5, characterized in that: In the step (1), the carbonaceous reducing agent includes one or more of carbon black, petroleum coke powder, and graphite powder.
9. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 5, characterized in that: In the step (1), the binder includes one or more of phenolic resin, dextrin, pregelatinized starch, and white sugar.
10. The process for co-producing titanium nitride and ferrosilicon nitride according to claim 5, characterized in that: In the step (1), the solvent is alcohol or water.
Citation Information
Patent Citations
Method for producing low-carbon low-melting-point silicon-nitrogen alloy
CN105463230A
Method for producing carbon titanium nitride and titanium nitride powder through quick nitridation
CN108424147A